2014
DOI: 10.1111/clr.12497
|View full text |Cite
|
Sign up to set email alerts
|

Combined maxillary sinus floor elevation and endonasal endoscopic sinus surgery for coexisting inflammatory sinonasal pathologies: a one‐stage double‐team procedure

Abstract: We first report the promising outcomes of the double-team one-stage SFE+ESS procedure performed by a combined team of otorhinolaryngologist and maxillofacial surgeons, including on patients presenting with an infection of the sinuses at the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that presence of a cyst in the maxillary sinus does not affect prognosis of the sinus bone graft. In this study, the total implant survival rate was 97.0%, which is similar to rates reported in previous studies, in which Bio‐Oss was used along or as a composite graft with amounts of autogenous bone …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the total implant survival rate was 97.0%, which is similar to rates reported in previous studies, in which Bio-Oss was used along or as a composite graft with amounts of autogenous bone. 1,10 Although Caldwell-Lec surgery and endoscopic sinus surgery can be performed for complete cyst removal and to avoid recurrences, studies have proposed a period of 6 to 12 months for sinus augmentation after removal of an antral pseudocyst to allow for regeneration of new respiratory ciliated epithelium. 19,20 However, high complication rates and operative trauma can create challenges in terms of patient cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rather than two‐stage or even three‐stage procedures, we applied one‐stage surgery that completed AP removal, MSFA and immediate implant placement all at once in all patients for the first time. A similar study completed simultaneous treatment of sinus diseases, MSFA and delayed implant placement by otorhinolaryngologists and maxillofacial surgeons (Abu‐Ghanem et al, 2015). At an average 9.9‐month follow‐up, recovered sinus function and good integration of bone grafts were observed in all patients, indicating promising outcomes of two‐stage surgery.…”
Section: Discussionmentioning
confidence: 99%